The Institutional Learning and Change Initiative: an introduction - CGIAR Institutional Learning and Change Initiative (2005)
At a time of rapid environmental, social and technological change, the Institutional Learning and Change (ILAC) Initiative promotes critical reflection and improved ways of working within the Consultative Group on International Agricultural Research (CGIAR). The goal is to enhance the contribution of agricultural research to sustainable poverty reduction. The ILAC Initiative draws on the expanding body of knowledge encompassing complex adaptive systems, innovation processes, organizational learning and program evaluation, and promotes the examination of research paradigms, institutional norms, management practices and professional behaviours. The Initiative aims to improve agricultural research and development efforts in four key areas: a) developing the capacity of researchers and managers to lead their own learning and change efforts; b) promoting the development of management systems and practices that support continuous learning and change; c) supporting an organizational culture of learning and change; and d) fostering donor and system-level support for learning and change initiatives in CGIAR centres and programs. This Brief outlines the rationale for ILAC within the CGIAR, highlights the main features of the Initiative and briefly describes the expected results and benefits for the CGIAR.